Analisis Faktor-Faktor Brand Loyalty Smartphone Samsung di Sidoarjo - Almira Zakkiya Arofa; Nuruni Ika Kusuma Wardhani (Universitas Batanghari Jambi, 2022)
The rapid advancement of communication technology is characterized by a huge number of requests for various sorts of communication tools, resulting in increased rivalry in communication products such as smartphones. On the market, there are numerous smartphone brands. As a result, Samsung smartphones have a large market share. This study aimed to analyze how Brand Personality, Brand Love, and Brand Experience affect Samsung Smartphone Brand Loyalty in Sidoarjo Regency. This study employed a quantitative approach, with 90 respondents and a total of 90 samples evaluated. The sampling method employed a non-probability approach with a purposive sampling strategy, in which the sample was chosen depending on the researcher's criteria.The data processing technique used was Partial Least Square (PLS). The results revealed that (1) brand personality has no significant effect on brand loyalty, (2) brand love has a significant positive effect on brand loyalty on Samsung smartphones, (3) brand experience significant positive effect on brand experience on Samsung smartphones.